EFEKTIVITAS PENCARIAN RUTE RUMAH KOS DAN KONTRAKAN BERBASIS ALGORITMA DIJKSTRA DAN ASTAR - Moh Nur Latuconsina (Lambung Mangkurat University, 2021)
Today we live in a digital age, where all things in our life. Technological developments make the exchange of information so fast. How to get information is also very easy. The digital era that we are experiencing today actually goes hand in hand with the growth of the human population which is also increasing so fast. Technological sophistication has not been able to provide a significant solution regarding the need for a place to live. This has made the purchase price of a house more expensive, especially in the capital city and its surroundings. The higher the purchase price of a house makes many people prefer to live in a boarding house or rented house, this is because the rental price is relatively cheap instead of buying a house. For example, in the city of Jakarta, around the campus, there are many boarding houses and rented houses due to the large number of National University students from various regions throughout Indonesia. Therefore, in this study created a THE EFFECTIVENESS OF SEARCHING FOR KOS AND RENTAL HOUSE BASED ON THE ALGORITHM OF DIJKSTRA AND ASTAR